Exploring Partners, Parenting and Pregnancy Thinking in Late Adolescents and Young Adults with Inherited Metabolic Disorders - Albina Tummolo; Giulia Paterno; Rosa Carella; Livio Melpignano; Donatella De Giovanni (Pediatric Reports)
Introduction: The psychosocial impact of living with an Inherited Metabolic Disorder (IMD) is becoming increasingly relevant and can have a significant impact on planning the future, conditioning the reproductive decisions made during adolescence and young adulthood. The aim of this paper is to explore thoughts about partner choices, parenthood and pregnancy among adolescents and young adults affected by IMDs. Methods: A cross-sectional study was performed. A sample of 23 patients affected by a range of IMDs were interviewed. Twenty-two questions were provided, distinguished into four main themes: partners, parenthood, pregnancy and need for information. Results: More than half of participants (57%) reported insecurities about relationships and declared that they were single for this reason, with most (70%) having a hope of having children in the future, although with the awareness and fear that they could also be affected. Almost all females (90%) consider themselves able to carry a pregnancy in a way similar to other women. There was the common need for more information about their potential fertility and parenthood linked to their condition. Conclusion: Being diagnosed with an IMD can influence personal decisions regarding relationships and reproduction. The early identification of issues in these domains may enhance referrals for personalized interventions and build more focused support programmes.